Orthodontically Correction of A Class III Malocclusion without any Surgical Intervention in an adult Patient- A Case report. (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Aim: A case of class-III malocclusion with a prognathic mandible is presented. Treatment objective included, improving facial aesthetics, correction of anterior and posterior cross bite, establishing a stable occlusion and masticatory efficiency. Subject and Methods: The patient was a 17 years old girl who been classified as class-III malocclusion. Sequele included midface depress, anterior and posterior cross bite, reverse overbite 5.5mm and reverse over jet 2.5mm, masticatory had efficiency, crowding in upper anterior segment. The aim was to flare out the maxillary arch and bring the maxillary anterior dentition over the lower dentition and established stable occlusion by class-III Activator and standard edge wise appliance. Results: The anterior cross bite was corrected, with relative forward movement of point A. Case The profile of the patient was corrected and normal overbite and over jet established. A well balance lip profile was created and psychological impairment was eliminated. Conclusion: Correction of anterior cross bite improved the facial, dental and profile of the patients. These factors contributed to the maintenance of a long term occlusal stability. DOI: http://dx.doi.org/10.3329/bjodfo.v2i2.16163 Ban J Orthod & Dentofac Orthop, April 2012; Vol-2, No.2, 38-40